Predictors for the need for fasciotomy after arterial vascular trauma of the lower extremity. Issue 8 (August 2021) - Kluckner, Michaela; Gratl, Alexandra; Gruber, Leonhard; Frech, Andreas; Gummerer, Maria; Enzmann, Florian K.; Wipper, Sabine; Klocker, Josef
Highlights: Arterial vascular trauma of the lower extremity in 119 civilian patients was leading to a fasciotomy rate of 73.9%. The strongest predictors for fasciotomy was an ischaemia time with a cut-off >2.5 h with a fasciotomy rate in this group of 92.6%. Other predictors were a Rutherford category greater than IIa, disruption or occlusion of the vessel and trauma to the popliteal artery. Abstract: Introduction: Compartment syndrome of the lower extremity following arterial vascular trauma can cause irreversible damage to muscle as well as nerve tissue leading to long-term functional impairment of the extremity or worse limb loss. Prompt diagnosis and treatment of compartment syndrome is mandatory to preserve muscle tissue and prevent limb loss. The aim of the study was to analyze the fasciotomy rate of our patient cohort and to perform a predictors analysis for the need of fasciotomy. Material and Methods: In a retrospective study all patients treated for arterial vascular trauma since 1990 were identified. Demographics, clinical data and outcome were analysed. After separation in a fasciotomy and non-fasciotomy group, a Bayes Network was used to arrive at a predictor ranking for the need of fasciotomy via a gain ratio feature evaluation. Results: In the period of 28 years, 88 (73.9%) of a total of 119 patients, predominantly male (80.7%) and aged under 40 years (37.5 ± 17.5), required fasciotomy after arterial vascular trauma. Patients of the fasciotomy group presented at higher Rutherford categories (grade III 34.1% vs. 9.7%, p  = 0.005), varied in terms of the type of arterial vascular injury (dissection 25% vs. 61.3%, p <0.001, occlusion 15.9% vs. 0%, p  = 0.011) and showed prolonged hospitalization (35.17 ± 29.3 vs. 21.48±25.4, p  = 0.002). Ischaemia duration exceeding 2.5 h followed by the Rutherford grade IIa and greater, the site (popliteal artery segment 3), type (transection and occlusion), and mechanism of vascular trauma (work related accident over traffic and sports accidents), as well as the male gender presented as strong predictors for fasciotomy. Conclusions: Arterial vascular trauma requiring fasciotomy for compartment syndrome accounted for 73.9% of all cases. Immediate diagnosis and treatment is mandatory to prevent long-term functional impairment or limb loss. The above mentioned predictors should help identifying patients at risk for developing a compartment syndrome to provide best possible treatment.